Journalists as storytellers: Benefits and uses of established narrative techniques in news production (KULT_online, 2014)
In their guidebook, the journalists and journalism instructors Marie Lampert and Rolf Wespe provide an overview of how established storytelling techniques can be used in the construction of journalistic texts. The strategies for grabbing attention they present are based on proven and tested narrative techniques and are illustrated by numerous examples – which are directed at beginners rather than pros. Yet, this solid handbook lacks in critical reflection.